Porites fontanesii, a new species of hard coral (Scleractinia, Poritidae) from the southern Red Sea, the Gulf of Tadjoura, and the Gulf of Aden, and its phylogenetic relationships within the genus - Benzoni, Francesca; Stefani, Fabrizio (Zootaxa, 2012)
A new zooxanthellate reef-dwelling scleractinian coral species, Porites fontanesii sp. nov. (Scleractinia, Poritidae), is de-scribed. The examined material was collected from the Southern Red Sea, the Gulf of Tadjoura, and the Gulf of Aden.Porites fontanesii sp. nov. was most frequently observed along the Yemen south Red Sea and the north-western Gulf ofAden coasts. Although a complete molecular phylogeny of Porites is not available yet, the relationships between P. fon-tanesii sp. nov. and twenty other species of the genus were explored through analysis of the available rDNA sequences.Porites fontanesii sp. nov. was seen to be a distinct species basal to, and well divergent from, one of the two main clades so far identified in the genus rDNA phylogeny.